Circulating and disseminated tumour cells — mechanisms of immune surveillance and escape - Mohme, Malte; Riethdorf, Sabine; Pantel, Klaus (Nature reviews. Clinical oncology, 2017)
Key Points Cancer cells leaving the immunosuppressive microenvironment of the primary tumour become vulnerable to immune surveillance and require mechanisms of escape from immune-mediated elimination if they are to form metastases Circulating tumour cells (CTCs) and disseminated tumour cells (DTCs) are often detectable in the peripheral blood and bone marrow, respectively, of patients with any of a range of different malignancies CTCs and DTCs exploit a large variety of immune-escape mechanisms, including alterations in the expression of MHC molecules, NK-cell ligands, FAS, FAS ligand (FASL), and immune-checkpoint molecules, such as CD47 and programmed cell death 1 ligand 1 (PD-L1) CTC homing to distant organs can be supported by direct interactions with immune cells during the process of extravasation, and by the effects of inflammatory cytokines in the target organ Future studies must address the important question of how the immune system shapes the molecular composition of CTCs and DTCs during cancer dormancy and metastatic progression To form metastases, cancer cells must leave the immunosuppressive tumour microenvironment and traffic, predominantly in the circulation, to new tissue sites, where they must then expand. During this process, the tumour cells are open to attack by the immune system. This Review highlights the possible mechanisms used by circulating tumour cells in the blood and disseminated tumour cells in other tissues to evade, escape, or subvert the immune system in order to survive and form metastatic lesions. Metastatic spread of tumour cells is the main cause of cancer-related deaths. Understanding the mechanisms of tumour-cell dissemination has, therefore, become an important focus for cancer research. In patients with cancer, disseminated cancer cells are often detectable in the peripheral blood as circulating tumour cells (CTCs) and in the bone marrow or lymph nodes as disseminated tumour cells (DTCs). The identification and characterization of CTCs and DTCs has yielded important insights into the mechanisms of metastasis, resulting in a better understanding of the molecular alterations and profiles underlying drug resistance. Given the expanding role of immunotherapies in the treatment of cancer, interactions between tumour cells and immune cells are the subject of intense research. Theoretically, cancer cells that exit the primary tumour site — leaving the protection of the typically immunosuppressive tumour microenvironment — will be more vulnerable to attack by immune effector cells; thus, the survival of tumour cells after dissemination might be the 'Achilles' heel' of metastatic progression. In this Review, we discuss findings relating to the interactions of CTCs and DTCs with the immune system, in the context of cancer immuno-editing, evasion from immune surveillance, and formation of metastases.